Reference Ranges and Distribution of Placental Volume by 3‐Dimensional Virtual Organ Computer‐Aided Analysis Between 11 Weeks and 13 Weeks 6 Days. (1st August 2013) - Guyomard, Aurélie; Macé, Guillaume; Ferdynus, Cyril; Franceschini, Carole; Rousseau, Thierry; Sagot, Paul
Abstract : Objectives: The purpose of this study was to determine the feasibility, reproducibility, and distribution of placental volume measurements according to the crown‐rump length between 11 weeks and 13 weeks 6 days. Methods: Images were acquired in 128 pregnancies followed in Burgundy during first‐trimester screening sonography using an abdominal 3‐dimensional transducer. The placental volume was then calculated by the virtual organ computer‐aided analysis method with a rotation angle of 30° by a single operator. Results: Placental volumes ranged from 33.3 to 107.6 cm 3 with a mean ± SD of 62.3 ± 14.8 cm 3 ; the 5th and 10th percentiles were 38.0 and 44.20 cm 3, respectively, whereas the 90th and 95th percentiles were 80.25 and 86.68 cm 3 . An exponential relationship was found between placental volume and crown‐rump length: ln placental volume = 0.018 × crown‐rump length + 2.93425; ln SD = 0.15; r 2 = 0.58. Finally, the mean placental quotient, defined as the ratio of placental volume to crown‐rump length, was 1 ± 0.1 cm 3 /mm; the respective percentile values were 0.74, 0.81, 1.18, and 1.29 cm 3 /mm. No associations were found between parity or smoking and the placental quotient or between obesity and the placental quotient. Intraobserver reproducibility was good, with a mean difference of 0.2 cm 3 . Conclusions: Measurement of placental volume between 11 weeks and 13 weeks 6 days is reliable and reproducible and correlates strongly with crown‐rump length.